Multi-agent system for credit scoring - Silva, Fábio (2011)
The use of multi-agent systems to solve complex problems in today’s world is not a new approach. Nevertheless, there has been a growing interest in using its properties in conjunction with machine learning and data mining techniques in order to build smarter systems. A multi-agent system able to classify and recommend attribute values in an instance of a dataset is presented and intended to provide to the end user a better understanding of both the classification in the dataset and client possibilities to obtain a good classification. The multi-agent system presented will have the ability to classify a user credit application and suggest different values for its attributes under assessment.